Significant soil : settler colonialism and Japan's urban empire in Manchuria - O'Dwyer, Emer Sinéad (Harvard East Asian monographs, 2015)
"Traces the history of Japan's prewar Manchurian empire over four decades, mapping how South Manchuria--and especially its principal city, Dairen--was naturalized as a Japanese space and revealing how this process ultimately contributed to the success of the Japanese army's early 1930s takeover of Manchuria. Simultaneously, the book demonstrates the conditional nature of popular support for Kwantung Army state-building in Manchukuo, highlighting the settlers' determination that the Kwantung Leasehold and Railway Zone remain separate from the project of total empire"--Provided by the publisher